Elevated Alanine Transaminase-to-Platelet Index (APRI) Is Associated with Obesity and Distinct Forms of Dyslipidemia: A Retrospective Cross-Sectional Study - Alshuweishi, Yazeed; Alfayez, Dalal; Almufarrih, Abdulmalik A.; Abudawood, Arwa; Alyami, Hanan; Alshuweishi, Faisal A.; Al-Sheikh, Yazeed A.; Alfhili, Mohammad A. (Journal of clinical medicine, 2024)
Background: Obesity is a pathological condition and a major risk factor for dyslipidemia, type 2 diabetes, and non-alcoholic fatty liver disease. Recent research highlighted the association of non-invasive serum markers with these conditions but the clinical utility of ALT APRI in obesity and its relationship with dyslipidemia remain unexplored. Methods: We examined the association of ALT APRI in 165 non-diabetic adults stratified by BMI and serum lipid parameters. Results: Obese subjects had significantly higher APRI than lean subjects, with an area under the curve (AUC) of 0.65 (p = 0.019). Medians of APRI were significantly increased in subjects with high TG, TG/HDL, TC/HDL, and LDL/HDL and low HDL. Notably, all lipid parameters and ratios were significantly elevated in the highest APRI tertile, compared with patients in the lowest tertile. APRI was weakly yet significantly correlated with BMI (R2 = 0.032, p = 0.022), HDL (R2 = 0.071), TG/HDL (R2 = 0.031), TC/HDL (R2 = 0.063), LDL/HDL (R2 = 0.072), and TyG index (R2 = 0.081). While APRI only showed a discriminating capacity for HDL (AUC: 0.69, p = 0.003), TG/HDL (AUC: 0.63, p = 0.020), LDL/HDL (AUC: 0.68, p < 0.001), and TyG index (AUC: 0.65, p = 0.037), the highest diagnostic performance of APRI was observed with TC/HDL (AUC: 0.74, p < 0.001). Additionally, APRI was a risk factor for high TG (OR: 1.6, p = 0.028), low HDL (OR: 2.7, p = 0.0002), high TG/HDL (OR: 1.94, p = 0.0011), high TC/HDL (OR: 2.3, p < 0.0001), high LDL/HDL (OR: 2.2, p = 0.0001), and high TyG index (OR: 2.1, p = 0.008). Conclusions: Our findings argue for the role of APRI as a potential marker for obesity and dyslipidemia, which requires further confirmation in longitudinal studies.